PREVALENCE OF PERIPHERAL ARTERIAL DISEASES IN PATIENT WITH CORONARY ARTERY DISEASES OF INDIAN ORIGIN. (8th October 2012) - Saran, RK; Bhagat, RL; Narain, VS; Dwivedi, SK; Puri, A; Sharad, Chandra; Sethi, R; Saran, RK
Abstract : Objectives: The prevalence of Peripheral Arterial Diseases (PAD) in patients with Coronary Artery Diseases (CAD) in western world ranges from 10% to 30%. The prevalence of PAD in patients of CAD in Indian population is not known. Methods: Patients of acute coronary syndrome ST Elevation Myocardial Infarction (STEMI) & Non ST Elevation Myocardial Infarction (NSTEMI) and patients with chronic stable angina with angiographically proven CAD were included in study. Ankle brachial index (ABI) was measured at the time of discharge. Measurement of the ABI was performed by using a blood pressure (BP) cuff and handheld Doppler device with a vascular probe (Minidop D580). ABI less than 0.9 was considered abnormal. Results: A total of 207 (85% males, mean age 55±11 years) patients of CAD were included in the study. Acute STEMI were 62% (n=128), NSTEMI were 29% (n=60) & stable angina were 9% (n=18). History of smoking was present in 46.4% (n=96) patients, hypertension in 33.85% (n=70) patients, tobacco chewing in 31.9% (n=66) and diabetes mellitus in 30.4% (n=63). PAD as defined by ABI less than 0.9 was noted in 7.7% (n=16) patients. Patient with low ABI group had higher mean age compared to normal ABI group (60±11 years vs 54±11 years: z=2.007; p=0.045). The prevalence of diabetes and hypertension was significantly higher in patients with low ABI compared to normal ABI Hypertension 68.8% vs 30.9%; p=0.003 & Diabetes 68.8% vs 27.2%; p=0.001. The incidence of triple vessel diseases was higher in patients with low ABI (18.8% vs 5.8% p<0.001). Conclusions: The prevalence of peripheral arterial disease as judged by ankle brachial index in known patients of CAD is much lower (7.7%) in our country. Compared to the patients with normal ABI, low ABI patients were older and had significant association with conventional risk factors.